A reportagem jornalística e a compreensão como método: um estudo da série “Um mundo de muros”, Da Folha de S. Paulo - Klautau, Carolina Moura; Künsch, Dimas A.; Carraro, Renata (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The subject of our study in this essay is “A World of Walls”, a series of reporting stories published by brazilian daily newspaper Folha de S. Paulo. The series confirms the privileged place of reporting in interpretive journalism and expresses a thought based on the theoretical and epistemological notion of comprehension – meaning to embrace, to integrate, to included, to contextualize, to look upon the facts and events of today in its complexity. We base our discussion on elements of theory of reporting that are helpful to show the virtualities of reportage from the past and the present that may be improved with the ICT resources.